Uma leitura da Gaudium et Spes na perspectiva de mulheres latino-americanas - Domezi, Maria Cecília (Revista eclesiástica brasileira, 2006)
In the light of the Syrian-Phoenician woman’s message (Mk:7:24-30 and Mt.15:21-28) and with a critical awareness of gender, we seek a greater understanding of the document Gaudium et Spes because of its humanistic and direct approach to the process of modernity. Although in the Vatican II Council patriarchalism may have persisted in the Catholic practices, there have been efforts to overcome it and, in particular, important symbolical possibilities emerged in the perspective of gender equality and in the valorization of human sexuality.